PERANCANGAN DAN PEMBUATAN MESIN PEMIPIH BUAH KOLANG-KALING - Saleh, Agus; Ramdani, Rizki; Azhary, Denny; Ginting, Edison; Wachidin, Wachidin (Jurnal TEDC, 2024)
The development of sugar palm plants in Indonesia is very prospective. Can increase farmers' income from sugar palm farming, as well as preserving natural resources and the environment. The application of post-harvest technology for palm fruit that is not yet optimal causes the production of palm fruit to be very low. So researchers are interested in designing a tool for processing kolang kaling. The general aim of this research is to design a fruit processing machine for kolang kaling fruit. The specific aim of this research is to analyze, design and build flatteners for kolang kaling machines. This research method uses the experimental method with a combination of qualitative and quantitative approaches, while the data analysis technique used uses quantitative techniques. The measurement results show that the length of time for peeling, flattening and separating palm seeds required by the designed machine is faster than manually. The time required by the machine designed to peel 10 kg of palm fruit is an average of 38.6 seconds, while the manual requires 470 seconds. After stripping, the flattening process is carried out. The results obtained in one rotation of the flattening shaft are that it can flatten 180 palm fronds in a time of 2 seconds. In conclusion, the designed palm fruit flattening machine can flatten palm fruit without taking a long time. The time required to peel palm fruit using a designed machine is more effective than the manual method.